Improvements in phenotype studies of hemoglobin disorders brought by advances in reversed‐phase chromatography of globin chains. (11th August 2014) - Riou, J.; Pissard, S.; Goossens, M.; Wajcman, H.
Summary Introduction Phenotype studies still occupy a key position in the diagnosis of hemoglobin (Hb) disorders. Material and Methods In addition to the conventional methods for diagnosis of Hb disorders which are mostly based on differences in charge of the Hb molecules, some progresses have been brought by studying other properties of the globin chains. Among those, difference in hydrophobicity that may be investigated by reversed‐phase HPLC (RP‐HPLC) discriminates between variants displaying identical charges. Results In this study, we show how an update of this method allows to recognize an α‐chain variant from a γ‐chain variant, a problem frequently during neonatal screening. We illustrate that RP‐HPLC may also unravel unclear phenotypes which are modified by the presence of an additional variant not detected by the conventional methods, and help to characterize rare mutants. Also we show that it allows a clear distinction between variants with identical electrophoretical charges as exemplified by Hb Lepore Boston–Washington and Lepore Baltimore. Conclusions In view of our results, RP‐HPLC is a technique that needs to be used as a second step in the general strategy for a correct characterization of Hb variants.